Dual Function of NAC072 in ABF3-Mediated ABA-Responsive Gene Regulation in Arabidopsis - Li, Xiaoyun; Li, Xiaoling; Li, Meijuan; Yan, Youcheng; Liu, Xu; Li, Ling (Frontiers in Plant Science, 2016)
The NAM, ATAF1/2, and CUC2 (NAC) domain proteins play various roles in plant growth and stress responses. Arabidopsis NAC transcription factor NAC072 has been reported as a transcriptional activator in ABA-responsive gene expression. However, the exact function of NAC072 in ABA signaling is still elusive. In this study, we present evidence for the interrelation between NAC072 and ABA-responsive element binding factor 3 (ABF3) that act as a positive regulator of ABA-responsive gene expression in Arabidopsis. The transcript of NAC072 is up-regulated by ABF3 in ABA response, and NAC072 protein interacts with ABF3. Enhanced ABA sensitivity occurs in nac072 mutant plants that overexpressed ABF3. However, overexpression of NAC072 weakened the ABA sensitivity in the abf3 mutant plants, but instead of recovering the ABA sensitivity of abf3. NAC072 and ABF3 cooperate to regulate RD29A expression, but are antagonistic when regulating RD29B expression. Therefore, NAC072 displays a dual function in ABF3-mediated ABA-responsive gene regulation.